The effect of different levels of training speed and accuracy in the development of performance skill scoring football - Abd Elkhalek, Sirhank (Journal of Physical Education, 2015)
The major developments in today’s world of science in all fields, including the field of sports led to outstanding sports achievements in all events, including football, and this sound emanated from the educational and scientific programming. Football is one of the sporting events granulocytes is has a lot of followers and persons with competence and experience to continuous research and hard work, and as a result sought these to improve this game and find the most effective ways and methods of educational training to win the game, which requires the introduction of the ball in the goal and this is not achieved by accident but the fruit of coach efficient effort, use the best scientific methods in order to develop scoring skill with his players, (and is the skill scoring football of the most basic skills importance because of its significant role in the achievement of winning the match and I’ve found through hundreds of games and higher levels of analysis that it is difficult The team loses if it leads towards a successful ten Tahedavat goal